The Role of Virtual Reality in Psychiatric Treatment: A Literature Review - Şişik, Ravza Nur; Emre, Ilkim Ecem (SAFE-Network, 2025)
Virtual reality (VR) is one of the immersive breakthroughs of rapidly growing technology. This VR technology, offers a 3-dimensional virtual environment to users while enabling interaction with this environment in various ways. VR can be seen in various sectors, including mental health care. Virtual Reality Exposure Therapy (VRET) has been established as an innovative approach for treating psychiatric disorders like social anxiety, obsessive-compulsive disorder (OCD), post-traumatic disorder, phobias, and other disorders (psychosis, functional neurological disorder (FND), and neuropsychological disorders) by offering individuals more controlled, interactive virtual environments that simulate triggering situations. In this review, the role of VR as a psychiatric treatment is explored. In total 50 articles were reviewed and reported in the study. Although the findings are promising, some limitations and challenges are detected. One of the concerns is relapse rates; no detailed studies are addressing it. In addition, in studies, cybersickness is reported, which can cause dizziness, nausea, and headache. In conclusion, while studies support VRET’s effectiveness, it is necessary to investigate further its long-term effects. Future studies should concentrate on conducting larger clinical trials and incorporating VR into standard therapeutic practices to fully harness its potential in treating mental health issues.